1999
DOI: 10.1002/etc.5620180305
|View full text |Cite
|
Sign up to set email alerts
|

Lethality and bioaccumulation of 4‐nonylphenol in bluegill sunfish in littoral enclosures

Abstract: Abstract-Toxicity and bioaccumulation in bluegill sunfish (Lepomis macrochirus) of 4-nonylphenol (NP), a common precursor and degradation intermediate of certain nonionic surfactants, were evaluated in a set of 18 aquatic mesocosms (littoral enclosures) in northeastern Minnesota. Nonylphenol was applied to enclosures every 48 h over a 20-d period (11 applications) at rates of 3, 30, 100, and 300 g/L. Additional enclosures served as untreated controls. Maximum NP levels in the integrated water column 2 h after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…Tissue concentrations in both species decreased rapidly when they were placed in clean water for up to 8 h after 96 h of exposure. The process of rapid uptake and steady state of nonylphenol followed by its rapid elimination in both fathead minnows and bluegills was similarly observed for freshwater [33][34][35] and saltwater organisms [6].…”
Section: Bioconcentration Testsmentioning
confidence: 56%
“…Tissue concentrations in both species decreased rapidly when they were placed in clean water for up to 8 h after 96 h of exposure. The process of rapid uptake and steady state of nonylphenol followed by its rapid elimination in both fathead minnows and bluegills was similarly observed for freshwater [33][34][35] and saltwater organisms [6].…”
Section: Bioconcentration Testsmentioning
confidence: 56%
“…NP may be one of the more dangerous EDCs owing to its toxicity, persistence, estrogenic effects, and abilities to bioconcentrate, bioaccumulate, and biomagnify in the environment (Liber et al, 1999;Tsuda et al, 2002). Surveys worldwide have detected NP in surface water, sediments, and industrial effluents (Blackburn & Waldock, 1995;Bennie et al, 1997;Tsuda et al, 2002).…”
Section: Downloaded By [New York University] At 22:45 07 December 2014mentioning
confidence: 99%
“…NP is a degradation product of a class of chemicals referred to as nonylphenol ethoxylates, which are part of a broader group of compounds known as alkylphenol ethoxylates. Nonylphenol ethoxylates are nonionic surfactants used in pesticides, spermicides, cleaning agents, textiles, various agricultural chemicals, plastics, and paper products (Liber et al, 1999;John et al, 2000). NP is an endocrine-disrupting chemical (EDC) (Roy et al, 1997;Choi et al, 2004) and may be one of the more critical metabolites of nonylphenol ethoxylates because of its toxicity, persistence, estrogenic effects, and abilities to bioconcentrate, bioaccumulate, and biomagnify in the environment (Liber et al, 1999;Tsuda et al, 2002).…”
mentioning
confidence: 99%
“…In an integrated evaluation of the persistence and effects of NP in a littoral enclosure, Liber et al [83,84] demonstrated that NP in water had a relatively short half life (≤1.2 d), whereas in sediment and macrophytes it was substantially longer (28 to 104 d and 8 to 13 d, respectively). These authors were not able to measure the half life in zooplankton and fish, but they report high survival rates.…”
Section: Impact On Ecosystemsmentioning
confidence: 99%